2004
DOI: 10.1002/ejlt.200400992
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the concentration of acrylamide during deep‐fat frying of potatoes

Abstract: Factors affecting the concentration of acrylamide during deep-fat frying of potatoesThe paper describes the effect of different factors influencing the concentration of acrylamide in deep-fat fried potato products. In French fries the amount of acrylamide increased with the temperature as well as the frying time, especially at temperatures higher than 175 7C. The increase of acrylamide with the time followed a linear function, whereas a non-linear relationship was given with the temperature of frying. As a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(136 citation statements)
references
References 18 publications
(19 reference statements)
11
120
2
3
Order By: Relevance
“…glucose plus fructose) and acrylamide levels for a particular time and temperature combination. This assumption is supported by previous research conducted by Amrein et al (2003Amrein et al ( , 2004b and Matthaus et al (2004). This method enables the calculation of an estimate of the level of acrylamide resulting from a particular time temperature regime and for a given level of reducing sugar in the raw potato.…”
Section: French Fry Productionsupporting
confidence: 63%
See 3 more Smart Citations
“…glucose plus fructose) and acrylamide levels for a particular time and temperature combination. This assumption is supported by previous research conducted by Amrein et al (2003Amrein et al ( , 2004b and Matthaus et al (2004). This method enables the calculation of an estimate of the level of acrylamide resulting from a particular time temperature regime and for a given level of reducing sugar in the raw potato.…”
Section: French Fry Productionsupporting
confidence: 63%
“…Several studies reported a strong correlation between reducing sugars and final acrylamide levels (Amrein et al, 2004b, Matthaus, Hasse andVosmann, 2004). Given the scientific evidence of a strong correlation between glucose and fructose levels and acrylamide formation, the initial focus of the model was on levels of reducing sugars in raw potatoes and the effect the various processes during French fry and crisp production have on reducing sugar levels.…”
Section: Reducing Sugarsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature and moisture levels in the food substrate are also other factors that affect ACR formation. While temperature has been discussed in the preceding section, Matthaus et al [32] reported that a quick reduction of the water content in the outer layers of the product (as a consequence of high temperatures) favours ACR formation.…”
Section: Substrate Compositionmentioning
confidence: 98%